مسائل أصول التفسير في كتب علوم القرآن (الإتقان في علوم القرآن للإمام جلال الدين السيوطي – أنموذجا - عطر, نصیرة (University of eloued جامعة الوادي, 2016)
الحمد لله رب العالمين والصلاة والسلام على خاتم الأنبياء والمرسلين المبعوث رحمة للعالمين وعلى آله وصحبه أجمعين وبعد . فإن هذا البحث بعنوان :مسائل أصول التفسير في كتب علوم القران "الإتقان في علوم القرآن للإمام جلال الدين السيوطي – أنموذجا-".وقد احتوى البحث على ثلاثة فصول، ففي الفصل التمهيدي بينت معنى أصول التفسير ومراحل نشأة هذا العلم، ثم ترجمت للإمام السيوطي وعرفت بكتابه الإتقان، وفي الفصل الأول بينت بعض مباحث علوم القران التي لها علاقة بمسائل أصول التفسير، وبعض مسائل أصول التفسير التي ذكرت مباشرة في كتب علوم القران، وفي الفصل الثاني بينت أهم مسائل أصول التفسير التي ذكرت في كتاب الإتقان وهي طرق التفسير، الاختلاف في التفسير عند السلف قواعد في التفسير وقد خلص البحث إلى أن كتاب الإتقان كان من أكثر الكتب ذكرا لمسائل أصول التفPraise be to Allah and peace and blessings be upon the seal of the prophets and messengers sent as a mercy to the worlds and his family and companions and after. This research titled: Origins interpretation issues in the books of the "Koran Science "model perfection. Find three chapters have been contained. In the introductory chapter demonstrated the meaning of the assets of the explanation and the stages of the emergence of this science, then translated to the Imam Suyuti and I knew typing proficiency, and in the first quarter showed some Quranic sciences Investigation related to the issues of the assets of interpretation, and some of the assets of interpretation issues that were mentioned directly in wrote Quranic sciences, and in the second quarter showed the most important assets of interpretation issues that were mentioned in the book, a mastery ways of interpretation, the difference in interpretation of rules when advances in interpretation has research found out that the book was a mastery of the most male issues origins interpretation books.
ماستر علوم القران
Keywords: مسائل,أصول التفسير,كتب,علوم القرآن; Issues, the origins of interpretation, books, Quranic sciences